Nipple Discharge, Imaging Evaluation and therapeutic approaches (Prospective study to 172 patients) - Dr. Deaa Abdulkhlik Raheem; Dr. Hadeel Khaleel Mahmood; Dr. FIRAS M. MUTAAB (Zien Journals, 2024)
When diagnosing nipple discharge, the doctor has a significant problem. Multiple disorders (including intraductal papillomas, nipple discharge can be a sign of several medical conditions, including mammary duct ectasia, breast cancer, pituitary adenomas, breast abscesses/infections, and more. The potential correlation between nipple discharge and underlying cancer makes it an important medical and patient concern. More and more women are seeking medical advice for nipple discharge as the public's understanding of breast cancer grows. Determining the etiology, assessing the risk of malignancy, and planning therapy of the patient with nipple discharge requires a thorough clinical assessment. Mammography, breast ultrasonography, and perhaps galactography are all diagnostic tools that can assist the doctor in making a diagnosis and developing a treatment strategy. A central or single lactiferous duct excision may be recommended as the surgery to undergo when diagnosing breast disease. For breast cancer patients experiencing nipple discharge, the recommended course of treatment is either a modified radical mastectomy or breast-conservation therapy, which involves duct-lobular segmentectomy with sufficient, free margins (preferably greater than 1 cm), axillary lymph node dissection at levels I and II, and radiotherapy to the breasts. Methods and patients The research will begin in October 2020 and follow 172 patients at the teaching hospital until October 2021. This research just involved female participants. All of the patients who participated in our research reported nipple discharge as their primary complaint. All patients had clinical examinations, mammograms, ultrasounds, and cytology. Patients who reported with nipple discharge and a suspected breast lump were evaluated using Fine Needle Aspiration Cytology (FNAC) and a final histological investigation.
Keywords: final; nipple; discharge; mammograms